Sono-Magneto-Photocatalytic Activity of Nd-Bifeo3/Nife2o4 Heterostructures - Casagrande-Denardin, J (Elsevier B.V., 2023)
A series of Bi0.90Nd0.10FeO3/NiFe2O4 (Nd-BFO/NFO) nanocomposites were prepared via a simple hydrothermal method and utilized to achieve a high photocatalytic response by imposing the coupled multiple energy fields including the ultrasonic and magnetic field (MF) to the photocatalytic system. Compared to the individual energy sources, the coupled fields displayed an improved catalytic activity towards the degradation of methylene violet (MV). Markedly, the Nd-BFO/NFO nanocomposites showed almost complete degradation (98.3 %) of the pollutant by applying the 40 kHz of ultrasonic and 0.25 T of MFs simultaneously to the photocatalysis. The improved photocatalytic performance is attributed to the separation of charge carriers and their increased migration rate, which are caused by the piezoelectric effect of BFO produced by external ultrasonic and the Lorentz force by MFs respectively. © 2023 Elsevier B.V.